Potential role for age as a modulator of oral nitrate reductase activity - Ahmed, Khandaker Ahtesham; Kim, Kiyoung; Ricart, Karina; Van Der Pol, William; Qi, Xiaoping; Bamman, Marcas M.; Behrens, Christian; Fisher, Gordon; Boulton, Michael E.; Morrow, Casey; O'Neal, Pamela V.; Patel, Rakesh P. (Nitric oxide, 2021)
Reduction of salivary nitrate to nitrite by oral nitrate reductase (NR) expressing bacteria has emerged as an integral pathway in regulating nitric oxide (NO) homeostasis and signaling. The oral microbiome is critical for this pathway. Variations in this pathway may underlie variable responses in the magnitude by which dietary or therapeutic nitrate modulates NO-signaling. The relationships between oral microbes and NR activity, and the factors that affect this relationship remain unclear however. Using a cross-sectional study design, the objective of this study was to determine the relationships between oral microbes and oral NR activity using a protocol that directly measures initial NR activity. Tongue swabs were collected from 28 subjects ranging in age from 21 to 73y. Initial NR activity showed a bell-shaped dependence with age, with activity peaking at ~40-50y and being lower but similar between younger (20-30y) and older (51–73) individuals. Microbiome relative abundance and diversity analyses, using 16s sequencing, demonstrated differences across age and identified both NR expressing and non-expressing bacteria in modulating initial NR activity. Finally, initial NR activity was measured in 3mo and 13mo old C57BL/6J mice. No differences in bacterial number were observed. However initial NR activity was significantly (80%) lower in 13mo old mice. Collectively, these data suggest that age is a variable in NR activity and may modulate responsiveness to dietary nitrate. •Age may be a variable in oral nitrate reductase activity and modulate responsiveness to dietary nitrate.•Oral nitrate reductase activity may be maximal in middle-age.•Middle age individuals may benefit most from nitrate-dependent interventions to stimulate nitric oxide bioactivity.